SDHx mutations are associated with the PI3K-Akt signaling pathway in vagal paragangliomas - Snezhkina, Anastasiya; Fedorova, Maria; Ayupova, Asiya; Pudova, Elena; Kobelyatskaya, Anastasiya; Kalinin, Dmitry; Golovyuk, Alexander; Krasnov, George; Pavlov, Vladislav; Kudryavtseva, Anna (Archive of Oncology, 2023)
Background: Vagal paraganglioma (VPGL) is a very rare neuroendocrine tumor arising from the paraganglion associated with the vagus nerve. VPGL is mainly characterized by an asymptomatic course and slow growth. However, up to 19% of tumors can metastasize. Due to the rarity of this tumor, information about VPGL is limited to single cases and small sample sets; the data on molecular genetic features is extremely scarce.Methods: For the first time we have analyzed the enrichment of biological pathways associated with mutations in the SDHx genes in VPGLs. Bioinformatics analysis was performed based on the results of high-throughput transcriptome sequencing on an Illumina platform for 33 tumor tissues obtained from patients with vagal paragangliomas.Results: Eight pathways of the Kyoto Encyclopedia of Genes and Genomes (KEGG) database with gene overrepresentation (top-40 mode) have been identified. Significant changes were shown for the cancer-associated PI3K-Akt signaling pathway and interconnected pathways of focal adhesion and interaction of receptors with the extracellular matrix enriched by overexpressed genes.Conclusion: Our result indicates the association of SDHx mutations with changes in the PI3K-Akt signaling pathway in vagal paraganglioma. The potential mechanism of deregulation in this pathway could be linked with a state of pseudohypoxia induced by the dysfunction of succinate dehydrogenase due to mutations in the SDHx genes.Key words: Head and neck paraganglioma, vagal paraganglioma, SDHx mutations, high-throughput sequencing, transcriptome, PI3K-Akt signaling pathway.
Keywords: Head and neck paraganglioma, vagal paraganglioma, SDHx mutations, high-throughput sequencing, transcriptome, PI3K-Akt signaling pathway